Downregulation of SLC27A6 by DNA Hypermethylation Promotes Proliferation but Suppresses Metastasis of Nasopharyngeal Carcinoma Through Modulating Lipid Metabolism - Zhong, Xuemin; Yang, Yanping; Li, Bo; Liang, Pan; Huang, Yiying; Zheng, Qian; Wang, Yifang; Xiao, Xue; Mo, Yingxi; Zhang, Zhe; Zhou, Xiaoying; Huang, Guangwu; et al. (Frontiers in Oncology, 2022)
Lipid is the building block and an important source of energy, contributing to the malignant behavior of tumor cells. Recent studies suggested that lipid droplets (LDs) accumulations were associated with nasopharyngeal carcinoma (NPC) progression. Solute carrier family 27 member 6 (SLC27A6) mediates the cellular uptake of long-chain fatty acid (LCFA), a necessary lipid component. However, the functions of SLC27A6 in NPC remain unknown. Here, we found a significant reduction of SLC27A6 mRNA in NPC tissues compared with normal nasopharyngeal epithelia (NNE). The promoter methylation ratio of SLC27A6 was greater in NPC than in non-cancerous tissues. The demethylation reagent 5-aza-2’-deoxycytidine (5-aza-dC) remarkably restored the mRNA expression of SLC27A6, suggesting that this gene was downregulated in NPC owing to DNA promoter hypermethylation. Furthermore, SLC27A6 overexpression level in NPC cell lines led to significant suppression of cell proliferation, clonogenicity in vitro, and tumorigenesis in vivo. Higher SLC27A6 expression, on the other hand, promoted NPC cell migration and invasion. In particular, re-expression of SLC27A6 faciliated epithelial-mesenchymal transition (EMT) signals in xenograft tumors. Furthermore, we observed that SLC27A6 enhanced the intracellular amount of triglyceride (TG) and total cholesterol (T-CHO) in NPC cells, contributing to lipid biosynthesis and increasing metastatic potential. Notably, the mRNA level of SLC27A6 was positively correlated with cancer stem cell (CSC) markers, CD24 and CD44. In summary, DNA promoter hypermethylation downregulated the expression of SLC27A6. Furthermore, re-expression of SLC27A6 inhibited the growth capacity of NPC cells but strengthened the CSC markers. Our findings revealed the dual role of SLC27A6 in NPC and shed novel light on the link between lipid metabolism and CSC maintenance.